Core competencies in teaching and training for doctors in Scotland: a review of the literature and stakeholder survey. (June 2014) - Ross, Michael T.; Macrae, Claire; Scott, Jayne; Renwick, Lynne; Moffat, Mandy; Needham, Gillian; Scott, Hazel; Shippey, Ben; Jackson, Catherine; Edgar, Simon; Aitken, Debbie; Evans, Phillip; et al.
Abstract Background: The UK General Medical Council requires all registered doctors to be competent in all areas of their work, including teaching and training. Aims: The current research sought consensus on core competencies for all consultants and GPs involved in teaching and training in Scotland. Method: A draft list of 80 competencies was developed from the literature and made available as a survey to all consultants and GPs with teaching roles and all final year speciality trainees working in Scotland. Respondents rated the importance of each competency and provided free text comments. Results: There were 1026 responses. Eighteen competencies were rated as "high priority", and are recommended as a baseline for all doctors involved in teaching and training; 55 were rated as "medium priority", and are recommended in relation to specific teaching and training roles; and 7 were rated as "low priority". Free text responses suggested the topic was controversial and emotive, and emphasised the importance of further work to engage trainers. Conclusions: The findings appeared to have face validity, and it was felt these could be used as the basis for developing a "Scottish Trainer Framework" for doctors and others involved in teaching and training in Scotland.